Tracing priming effects in palsa peat carbon dynamics using a stable isotope-assisted metabolomics approach - Ayala-Ortiz, Christian; Hough, Moira; Eder, Elizabeth K.; Hoyt, David W.; Chu, Rosalie K.; Toyoda, Jason; Blazewicz, Steven J.; Crill, Patrick M.; Varner, Ruth; Saleska, Scott R.; Rich, Virginia I.; Tfaily, Malak M. (Frontiers in Molecular Biosciences, 2025)
IntroductionPeatlands store up to a third of global soil carbon, and in high latitudes their litter inputs are increasing and changing in composition under climate change. Although litter significantly influences peatland carbon and nutrient dynamics by changing the overall lability of peatland organic matter, the physicochemical mechanisms of this impact—and thus its full scope—remain poorly understood.MethodsWe applied multimodal metabolomics (UPLC-HRMS, 1H NMR) paired with 13C Stable Isotope-Assisted Metabolomics (SIAM) to track litter carbon and its potential priming effects on both existing soil organic matter and carbon gas emissions. Through this approach, we achieved molecule-specific tracking of carbon transformations at unprecedented detail.ResultsOur analysis revealed several key findings about carbon dynamics in palsa peat. Microbes responded rapidly to litter addition, producing a short-term increase in CO2 emissions, fueled nearly exclusively by transformations of litter carbon. Litter inputs significantly contributed to the organic nitrogen pool through amino acids and peptide derivatives, which served as readily accessible nutrient sources for microbial communities. We traced the fate of plant-derived polyphenols including flavonoids like rutin, finding evidence of their degradation through heterocyclic C-ring fission, while accumulation of some polyphenols suggested their role in limiting overall decomposition. The SIAM approach detected subtle molecular changes indicating minimal and transient priming activity that was undetectable through conventional gas measurements alone. This transient response was characterized by brief microbial stimulation followed by rapid return to baseline metabolism. Pre-existing peat organic matter remained relatively stable; significant priming of its consumption was not observed, nor was its structural alteration.DiscussionThis suggests that while litter inputs temporarily increase CO2 emissions, they don’t sustain long-term acceleration of stored carbon decomposition or substantially decrease peat’s carbon store capacity. Our findings demonstrate how technological advancements in analytical tools can provide a more detailed view of carbon cycling processes in complex soil systems.